Strategic Candidate Entry and Congressional Elections in the Era of Fox News. Issue 2 (11th October 2019) - Arceneaux, Kevin; Dunaway, Johanna; Johnson, Martin; Vander Wielen, Ryan J.
Abstract: Elections are designed to give voters the ability to hold elected officials accountable for their actions. For this to work, voters must be presented with credible alternatives from which to choose. In the United States, as in other weak‐party systems, the decision to challenge an incumbent representative rests with individual, strategic‐minded politicians who carefully weigh the available information. We investigate the role that one source of information—partisan media—plays in shaping electoral competition. We hypothesize that the haphazard expansion of the conservative Fox News Channel in the decade after its 1996 launch influenced congressional elections by affecting the decision calculus of high‐quality potential candidates. Using congressional district‐level data on the local availability of Fox News, we find that Fox News altered Republican potential candidates' perceptions about the vulnerability of Democratic incumbents, thereby changing their entry patterns.